(untitled) (Marketing Journal, 2025)
This article explores the modern theoretical foundations and practical models for attracting foreign direct investment (FDI) into a national economy. The study substantiates the application of the OLI model, competitive advantage theory, and the "flying geese" paradigm in managing investment flows. Uzbekistanʼs experience is analyzed in comparison with international frameworks, and effective strategic directions are proposed.